Teachers’ Perceptions on the Literacy Skills of 5th Grade Primary School Students During Covid-19 Pandemic in Mandailing Natal Regency - Suadi Suadi; Rahmi Seri Hanida; Parulian Siregar (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to discover the literacy skills of 5th grade primary school students during covid-19 outbreak in Mandailing Natal Regency based on teachers’ perceptions. Descriptive qualitative approach was applied with a simple quantitative support in form of percentages. The respondents in this study were 23 primary school teachers of fifth year class from 23 different primary schools located in 23 districs in Mandailing Natal Regency. To obtain the data, a semi structured interview was conducted adapted from four literacy skills consisting of listening, speaking, reading and writing. The obtained data subsequently were analyzed by thematic analysis based on specific separated themes. The findings demonstrated four results; (1) in listening skill, dominantly, 11 (48%) teachers thought that students’ literacy level is average and for higher level of listening 11 (48%) teachers shared low. (2) in speaking, 11 (48%) teachers stated average and for higher level, 13 (57%) teachers assumed low. (3) in reading, 12 (52%) teachers noted average, and (4) in writing, 11 (48%) teachers perceived average and for higher level, (52%) 12 of teacher-respondents responded that students’ literacy skills were average. Based on these results, it is highly expected to be worthwhile for teachers, lecturers, academician, stakeholders and public community to anticipate and to develop the students’ literacy development by supporting and facilitating the students’ fundamental needs such as children books, complete and comfortable school library, providing reading corner and ensuring teachers’ mastery on digital literacy platforms amidst covid-19 pandemic and in the coming years, as well.